Does internationalization moderate the effect of SMEs size, age, and other financial determinants on investment opportunities set? Evidence from Indonesia - Yuli Soesetio; Dyah Arini Rudhiningtyas; Sudarmiatin Sudarmiatin; Imam Mukhlis (University of Islam Malang, 2021)
Small and medium-sized enterprises (SMEs) are increasingly considering international expansion as one of the sustainable growth strategic options. This study aims to reveal how the effect of internationalization as a moderator of SMEs size, age, and other financial determinants toward investment opportunity set of SMEs that listed on the Indonesia Stock Exchange (IDX) from 2006 to 2020. Market to book asset ratio used as a proxy of investment opportunity set of SMEs. This study is one of the most important in the context of Indonesian SMEs as there were limited previous studies that have explored the internationalization factor. A total of 102 SMEs companies with 156 data observations were studied. A moderation regression analysis was used to test whether the determinants of the investment opportunity set were statistically significant. Surprisingly, the study found that the degree of internationalization has a moderating effect that weakens the relationship between SMEs age and size on investment opportunities set (market value ratio).